Community Empowerment Through The Gade Clean and Gold Program at Garbage Banks in Manggala District, Makassar City - Muhamad Falak Cahyadi; Muh. Yusril Ilyas; Usamah; Nur Fadillah; Khairin Nisa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This empowerment aims to provide education to the public about the importance of protecting the environment and provide an understanding of the economic value of managing waste. In the empowerment carried out using a method consisting of five stages, the first stage is selecting household waste, the second stage is depositing waste to the waste bank, the third stage is weighing the waste, the fourth stage is recording the value of the waste and the fifth stage is converting the waste value to gold savings. The results of this study indicate that community empowerment through the Gade Clean and Gold programs at the Garbage Bank has a significant impact on society, which can be seen from an economic, environmental and social perspective.